Glyphosate impacts on polyphenolic composition in grapevine (Vitis vinifera L.) berries and wine. (15th December 2016) - Donnini, Silvia; Tessarin, Paola; Ribera-Fonseca, Alejandra; Di Foggia, Michele; Parpinello, Giuseppina Paola; Rombolà, Adamo Domenico
Highlights: The effects of glyphosate on the quality of grape berries and wine were tested. Anthocyanins and pH were affected in berries from vines of glyphosate-treated plots. Compositional changes stimulate new investigations about the effects of glyphosate. Abstract: Glyphosate is the most widespread herbicide for weed management, being extensively used in viticulture. In this study we tested, under field conditions, the effects of glyphosate applications on the quality of berry and wine, from cv. Ancellotta ( Vitis vinifera L.), with particular regard to anthocyanin concentration and composition. Ripening and growth were monitored by analyzing berry technological parameters and weight. Additionally, microvinifications were performed, in order to analyze the concentration of anthocyanins, other flavonoids and phenolic acids in wine. Our findings indicated that, at harvest, both pH and anthocyanin concentration were significantly lower and titratable acidity higher in berries collected from vines of plots under glyphosate-treatment compared with those of non-treated parcels. Data suggest that treatment with glyphosate did not change the concentration of anthocyanins, other flavonoids and phenolic acids in the wine. Our results indicate that treatment with glyphosate may affect fruit metabolism and nutritional value in non-target plants.